2015
DOI: 10.1002/cb.1507
|View full text |Cite
|
Sign up to set email alerts
|

Children's consumption behavior in response to food product placements in movies

Abstract: Almost all research on the effects of product placements on children has focused on brand attitudes or behavioral intentions. Drawing on the important difference between attitudes or behavioral intentions on the one hand and actual behavior on the other, this paper tests the effects of brand placements on children's food consumption. Children from 6 to 14 years old were exposed to an excerpt of the popular movie Alvin and the Chipmunks, including placements for the product Cheese Balls. Three versions were cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 60 publications
1
86
2
3
Order By: Relevance
“…A number of randomised controlled studies, discussed in this paper, have shown significant effects on children's food behaviours after showing them unhealthy food advertising on TV [57,59,[63][64][65][66]79]; in advergames [67,69,70]; as product placements; [71,72] and as branding in the form of celebrity endorsements [73,75]. The one longitudinal study included in this paper also confirms this relationship [46].…”
Section: Experimental Studies Using Premium Offerssupporting
confidence: 67%
See 4 more Smart Citations
“…A number of randomised controlled studies, discussed in this paper, have shown significant effects on children's food behaviours after showing them unhealthy food advertising on TV [57,59,[63][64][65][66]79]; in advergames [67,69,70]; as product placements; [71,72] and as branding in the form of celebrity endorsements [73,75]. The one longitudinal study included in this paper also confirms this relationship [46].…”
Section: Experimental Studies Using Premium Offerssupporting
confidence: 67%
“…Given the choice of three similar snacks, 45% of children consumed the advertised product after high frequency exposure compared with 31% after lower frequency product placement and 18% in the control condition (p<0.05) [71]. Similarly, combined exposure to McDonald's food product placement plus McDonalds TV advertising saw children's (n=483, 9-15 years) intention to consume fast food increase from 18% (control condition) to 47% (single exposure) to 54% (p<0.05) [56].…”
Section: Experimental Studies Using Premium Offersmentioning
confidence: 98%
See 3 more Smart Citations